Optimasi Kendaraan Pengangkut Sampah di Kecamatan Kertapati Menggunakan Pemrograman Bilangan Bulat Biner 0 dan 1 - Eka Susanti; Endro Setyo Cahyono; Oki Dwipurwani (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2016)
Waste management in the district Kertapati done by the private sector and government. The authorities responsible for waste management is Palembang City Sanitation Department (DKKP). Waste is transported from the area TPS (Transit Depo) to landfill Sukawinatan use two types of vehicles, namely dump trucks and armroll. Analyzed optimality waste carrier vehicles with a total transport time constraints, the maximum capacity of conveyance and the maximum amount of waste that must be transported using integer programming binary 0 and 1. Integer programming binary 0 and 1 problem solved by the Branch and Bound Method. The maximum amount of waste that must be transported to the Lambung 87 is 7330 kg, Lambung 42 as much as 8850 kg and the Lambung 69 as much as 7770 kg. Dump truck and armroll are vehicles optimized for use on Lambung 42, 87 and 69.